An improved procedure for the Beckmann rearrangement of cyclobutanones. Issue 20 (16th May 2018) - Lachia, Mathilde; Richard, François; Bigler, Raphael; Kolleth-Krieger, Amandine; Dieckmann, Michael; Lumbroso, Alexandre; Karadeniz, Ulfet; Catak, Saron; De Mesmaeker, Alain
Graphical abstract: Highlights: An improved procedure for the Beckmann rearrangement of cyclobutanones has been developed. Experiments and DFT calculation support a rearrangement mechanism involving a tetrahedral intermediate. The generality of the method has been illustrated on 26 examples. Abstract: γ-Lactams are important building blocks for the synthesis of biologically active molecules and can easily be accessed via Beckmann rearrangement of cyclobutanones. However, Beckmann fragmentation is often a competing reaction for these strained ketones. We found that performing the Beckmann rearrangement with Tamura's reagent in the presence of aqueous HCl suppresses the undesired fragmentation reaction. This improved procedure was applied to a broad scope of substrates affording monocyclic, bicyclic, tricyclic or spirocyclic lactams. Our experimental results and DFT calculations suggest that the mechanism of the rearrangement probably involves a tetrahedral intermediate and doesn't proceed via oxime fragmentation as in a classical Beckmann rearrangement.